2017
DOI: 10.1111/jfpp.13351
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of exopolysaccharide producer lactic acid bacteria from Turkish yogurt

Abstract: Lactic acid bacteria (LAB) were isolated from traditional yogurt samples and genotypic characterization of these isolates revealed the presence of 21 distinct LAB strains belonging to Lactobacillus delbrueckii subsp. bulgaricus, Streptococcus thermophilus, Leuconostoc mesenteroides, and Lactobacillus plantarum as new LAB strains. Determination of the exopolysaccharide (EPS) production characteristics of the selected strains of each species revealed that all strains possessed at least one gene required for both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…Lb. brevis E25 was shown to produce a homopolymeric glucan type EPS consisting only glucose in its repeating unit [8] which agrees with the data reported previously [18] [3], [4]. In contrast some researchers report that some strains may produce heteropolymeric EPS with glucose and galactose in its repeating unit structure.…”
Section: Eps Producer Lab Strainssupporting
confidence: 89%
“…Lb. brevis E25 was shown to produce a homopolymeric glucan type EPS consisting only glucose in its repeating unit [8] which agrees with the data reported previously [18] [3], [4]. In contrast some researchers report that some strains may produce heteropolymeric EPS with glucose and galactose in its repeating unit structure.…”
Section: Eps Producer Lab Strainssupporting
confidence: 89%
“…L. plantarum strains can produce exopolysaccharide (EPS), a macromolecule composed of monosaccharide residues of sugar and sugar derivatives. EPS can act as an important factor in the physicochemical and rheological properties of yogurt due to its role as a natural concentrate agent and stabilizer [ 34 , 35 ]. Nambiar et al [ 36 ] have reported that EPS isolated from L. plantarum HM47 has high thermal stability and that it can enhance the texture of yogurt at a low pH (4.0).…”
Section: Resultsmentioning
confidence: 99%
“…The column temperature was kept constant at 25°C and deionized water was used as mobile phase. Sugars such as glucose, sucrose, fructose, xylose, arabinose were used to create the standard calibration curve (Ispirli and Dertli, 2018).…”
Section: Determination Of Sugar Content Of Sourdoughsmentioning
confidence: 99%